CRITICAL REVIEW OF TASKS IN ENGLISH TEXTBOOK “WHEN ENGLISH RINGS A BELL” - Aryani Aryani; Ikhsanudin Ikhsanudin; Regina Regina (ICoTE Proceedings, 2018)
Textbook plays an important role in English language teaching. Therefore evaluating a textbook is needed. It is interesting to analyse the newest textbook provided by the government due to it is used as a compulsory textbook. This study used a framework proposed by Littlejohn (2011). It is a subjective analysis level. The study focused on three key aspects of tasks; (1) what is the learners expected to do; (2) who are the learners to work with; and (3) what is the content focus for.  This was a qualitative content analysis study. The data of the research is "When English Rings A Bell" textbook.  It is used on the seventh-grade level. The data was collected using the analysis tasks sheet.  The result of the study has shown that the tasks presented were relevant to the requirements regarding Littlejohn’s framework. Based on the findings, it suggested that the materials developer should enrich presented ELT materials with various tasks.